Analysis of information structure modeling methods - Kuchuk, N.; Kotova, O. (ФОП Петров В.В., 2022)
A mathematical model is often used to analyze the information structure of a network. This model has the form of queuing networks. Queuing network – This is a system that performs the service of incoming requests to it. The main elements of the system are the input flow of applications, service channels, the queue of applications, the output flow of applications. Service requests arrive at discrete (constant or random) time intervals. It is important to know the law of distribution of the incoming flow. The channels needed to serve these applications. Service lasts for a while, constant or occasional
Keywords: Queuing network